Selected letters - Olson, Charles, 1910-1970 (University of California Press, 2000)
"In this volume, edited and annotated by Ralph Maud, we see Olson at the height of his powers and also at his most human. The nearly two hundred letters, selected from a known three thousand, demonstrate the wide range of Olson's interests and the depth of his concern for the future. As we read through the letters, which span the years from 1931, when Olson was an undergraduate in college, to his death in 1970, a fascinating portrait of this complex poet and thinker emerges."--Jacket